(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Family economic education plays an important role in shaping children’s economic behavior from an early age. Amid growing environmental sustainability issues, Green Economy values can be instilled through habits of frugality, wise consumption, and responsible resource management. This study aims to analyze the role of housewives in teaching Green Economy values to children through family economic education. The study uses a qualitative approach with a phenomenological design conducted in Rimbo Bujang District. The research informants consist of housewives and children. Data were collected through interviews, observations, and documentation, then analyzed using the Miles and Huberman model with the help of NVivo 12. Data validity was tested through source and technique triangulation. The research results show that housewives play a role as educators, role models, guides, and supervisors in instilling Green Economy values. This process is carried out through setting an example, habituation, communication, and involving children in managing family finances. The impact is seen in children’s habits of using money according to needs, saving, conserving electricity and water, and reusing items that can still be used. This study concludes that family economic education can be a strategic way to shape sustainable consumption behavior from an early age. These findings contribute to the development of family economic education studies based on sustainability.